Cover Feature: 3D 14N/1H Double Quantum/1H Single Quantum Correlation Solid‐State NMR for Probing the Parallel and Anti‐Parallel Beta‐Sheet Arrangement of Oligo‐Peptides at Natural Abundance (ChemPhysChem 15/2018). Issue 15 (24th July 2018) - Hong, You‐lee; Asakura, Tetsuo; Nishiyama, Yusuke
Abstract : The Cover Feature illustrates a method to identify the β‐sheet alignment through 3D 14 N/ 1 H double quantum (DQ)/ 1 H single quantum (SQ) solid‐state NMR at natural abundance. While the NH–NH correlation in 2D 1 H DQ/ 1 H SQ slices at 14 N shift of NH does not appear in the parallel β‐sheet alignment, the presence of NH–NH correlation identifies the anti‐parallel alignment. More information can be found in the Article by Y.‐l. Hong et al onpage 1852 in Issue 15, 2018 (DOI:10.1002/cphc.201800392 ).